SOME ISSUES OF PREVENTION OF VIOLENCE AGAINST WOMEN - Karaketova Dilnoza Yuldashevna (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the factors contributing to violence against women in Uzbekistan, focusing on economic, social, and cultural influences. It evaluates the effectiveness of legal measures, such as protection orders, and governmental programs designed to reduce domestic violence and support women at risk. Method: A sociological approach was employed, using surveys of female victims of violence to understand their social conditions and the characteristics of perpetrators. National crime data were analyzed to assess the scope and distribution of violence. The study also examined existing legislation and policies, including protective measures and rehabilitation programs, to evaluate their impact. Results: Violence against women in Uzbekistan is predominantly family-based, with high victimization rates among unemployed women over 30. Protective orders were found to significantly reduce further violence, with many families reconciling or resolving disputes. Legal frameworks, such as the Law on the Protection of Women from Harassment and Violence, played an important role in providing support. However, entrenched cultural norms and gender inequality continue to hinder progress. Novelty: This research highlights the role of economic dependency, cultural norms, and legal protection in shaping women's experiences of violence. It emphasizes the need for legal reforms and cultural shifts towards gender equality. The study proposes that stronger collaboration between government agencies and communities is crucial for combating violence and empowering women to achieve economic independence.